Respiratory Viral and Bacterial Exacerbations of COPD—The Role of the Airway Epithelium - Michelle E. Love; David Proud (Cells, 2022)
COPD is a leading cause of death worldwide, with acute exacerbations being a major contributor to disease morbidity and mortality. Indeed, exacerbations are associated with loss of lung function, and exacerbation frequency predicts poor prognosis. Respiratory infections are important triggers of acute exacerbations of COPD. This review examines the role of bacterial and viral infections, along with co-infections, in the pathogenesis of COPD exacerbations. Because the airway epithelium is the initial site of exposure both to cigarette smoke (or other pollutants) and to inhaled pathogens, we will focus on the role of airway epithelial cell responses in regulating the pathophysiology of exacerbations of COPD. This will include an examination of the interactions of cigarette smoke alone, and in combination with viral and bacterial exposures in modulating epithelial function and inflammatory and host defense pathways in the airways during COPD. Finally, we will briefly examine current and potential medication approaches to treat acute exacerbations of COPD triggered by respiratory infections.